Glider performance analysis and intermediate-fidelity modelling of underwater vehicles. (15th August 2020) - Deutsch, Clemens; Kuttenkeuler, Jakob; Melin, Tomas
Abstract: This paper analyses the transit performance of state-of-the-art underwater vehicles and presents an intermediate-fidelity steady-state flight mechanics model for qualitative performance assessment of underwater vehicles. Focusing on the comparison of underwater gliders and propeller-driven AUVs, a simple glide metric is presented and the transit performance of the legacy underwater gliders Slocum, Spray and Seaglider as well as propeller-modified versions thereof is evaluated. The evaluation is based on various data sets from wind tunnel tests and Computational Fluid Dynamics (CFD) studies, and shows that for the respective hull shapes gliding locomotion proves more efficient in ideal conditions. However, biofouling conditions inflict a double penalty on glider performance, rendering gliders inferior to propeller-driven vehicles. The Slocum data set is used to validate a steady-state flight mechanics model for qualitative performance prediction. It is shown that even simplistic models based on semi-empirical and analytical expressions can be successfully used for design optimization through parametrization. Being computationally efficient, the model can be a useful tool for design engineers in early design phases. The model is used to evaluate the effects of wing span on gliding efficiency, indicating that the current design of the Slocum glider is near-optimal. Highlights: Glide metric for underwater gliders is presented. Transit performance of underwater gliders and propeller-driven vehicles is evaluated. Underwater gliders are more efficient in ideal operating conditions. Propeller-driven vehicles are more efficient under consideration of biofouling. Transit performance can be estimated using intermediate-fidelity models.